2014
DOI: 10.1021/es501465h
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Level Description of the Sorptive Fractionation of a Fulvic Acid on Aluminum Oxide Using Electrospray Ionization Fourier Transform Mass Spectrometry

Abstract: We addressed here, by means of electrospray ionization mass spectrometry (ESI-MS) with ultrahigh resolution, the molecular level fractionation of a reference fulvic acid (SRFA) during its sorption at an alumina surface, taken as a model for surfaces of natural aluminum oxide hydrates. Examination of ESI-MS spectra of a native SRFA solution and of supernatants collected in sorption experiments at acidic pH showed that the ∼5700 compounds identified in the native solution were partitioned between the solution an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
70
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(86 citation statements)
references
References 32 publications
11
70
3
Order By: Relevance
“…This is also where WRT and the adsorption treatment diverge in their effect on DOM composition: Whereas unsaturated compounds are generally lost from solution in both processes, even fairly saturated compounds can be adsorbed as long as they have a high O/C (Figures 3c and S3). The observed adsorption of oxygen-rich compounds is in agreement with various other studies, where both highly oxidized aromatics (Coward et al, 2018;Fleury et al, 2017;Galindo & Del Nero, 2014;Lv et al, 2016), and in some cases also oxidized saturated, aliphatic compounds (Galindo & Del Nero, 2014;Avneri-Katz et al, 2017) were preferentially adsorbed. The preferential adsorption of oxygen-rich compounds indicates that the presence of carboxyl and hydroxyl functional groups may be important for adsorptive processes, as these groups allow for ligand exchange with oxide and hydroxide groups at the sorbent's surface (Chassé et al, 2015;Gu et al, 1995;Kaiser, 2003;Kaiser et al, 1997;Kothawala et al, 2012;Lv et al, 2016;Meier et al, 1999;Tipping, 1981b).…”
Section: Selective Dom Adsorptionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is also where WRT and the adsorption treatment diverge in their effect on DOM composition: Whereas unsaturated compounds are generally lost from solution in both processes, even fairly saturated compounds can be adsorbed as long as they have a high O/C (Figures 3c and S3). The observed adsorption of oxygen-rich compounds is in agreement with various other studies, where both highly oxidized aromatics (Coward et al, 2018;Fleury et al, 2017;Galindo & Del Nero, 2014;Lv et al, 2016), and in some cases also oxidized saturated, aliphatic compounds (Galindo & Del Nero, 2014;Avneri-Katz et al, 2017) were preferentially adsorbed. The preferential adsorption of oxygen-rich compounds indicates that the presence of carboxyl and hydroxyl functional groups may be important for adsorptive processes, as these groups allow for ligand exchange with oxide and hydroxide groups at the sorbent's surface (Chassé et al, 2015;Gu et al, 1995;Kaiser, 2003;Kaiser et al, 1997;Kothawala et al, 2012;Lv et al, 2016;Meier et al, 1999;Tipping, 1981b).…”
Section: Selective Dom Adsorptionsupporting
confidence: 92%
“…Unsaturated compounds (low H/C) are preferentially adsorbed while saturated compounds (high H/C) remain in solution. The same trend has been reported by studies using mass spectrometry to investigate the adsorption of Suwannee River fulvic acid from the International Humic Substances Society on alumina colloids (Galindo & Del Nero, 2014) and soil DOM, International Humic Substances Society Pahokee peat (Chassé et al, 2015) and peat DOM on iron oxyhydroxides (Lv et al, 2016), and soil fulvic acid on alumina colloids (Fleury et al, 2017). Accordingly, studies using other methods than mass spectrometry also found that compounds with low H/C such as polyphenols and aromatics are preferentially adsorbed (Kaiser, 2003;Kaiser et al, 1997;Kalbitz et al, 2005; Kothawala et al, Figure 6.…”
Section: Selective Dom Adsorptionsupporting
confidence: 78%
“…A removal of these unique high molecular weight polyaromatic DOM molecules by means of mineral adsorption or flocculation with iron (Philippe and Schaumann, 2014) or aluminum oxides (Galindo and Del Nero, 2014) after mixing with the high-sediment-load Solimões River is conceivable and corresponded to previous reports that between 4 % (Aucour et al, 2003) and 40 % of the DOC was removed at the confluence of the Rio Negro and Solimões. We were not able to sample the Solimões River directly, and hence a direct comparison between FT-ICR-MS results from the Rio Negro and Solimões were not achieved.…”
Section: Resultssupporting
confidence: 64%
“…A removal of these unique high molecular weight polyaromatic DOM molecules by means of mineral adsorption or flocculation with iron (Philippe and Schaumann, 2014) or aluminum oxides (Galindo and Del Nero, 2014) after mixing with the high-sediment-load Solimões River is conceivable and corresponded to previous reports that between 4 % (Aucour et al, 2003) and 40 % (Moreira-Turcq et al, 2003) of the DOC was removed at the confluence of the Rio Negro and Solimões. We were not able to sample the Solimões River directly, and hence a direct comparison between FT-ICR-MS results from the Rio Negro and Solimões were not achieved.…”
Section: Resultssupporting
confidence: 65%